Credit Bureau Licensing and Supervision : A Primer - World Bank (World Bank, Washington, DC, 2020)
In recent years, as more and more regulators have begun to assume the role of supervision and oversight over credit bureau(s), the World Bank Group has supported supervisors in understanding and carrying out their duties as it relates to this role. The WBG has supported the development of the credit bureau supervisory framework and the capacity to supervise these systems in several countries, including Morocco, the West African Monetary Union, Jordan, Bhutan, and the Bahamas. In addition, the WBG has provided light touch assistance on the supervision of credit bureaus in several Caribbean countries including Jamaica, Belize, the OECS, Guyana and Suriname. The WBG has facilitated study tours for regulators to markets where credit bureau supervision processes are established, thereby enabling the exchange of experiences and information between regulators. Such study tours include mock audits of the credit bureau in the host country, where possible. The mock audits provide the visiting regulators with an opportunity to mimic the processes that would be followed in case of an audit. This primer draws upon the WBG’s experience across various markets and intended to provide regulators, policymakers, practitioners and financial sector specialists with a general overview of what the licensing and supervision of a credit bureau entails.